The Approach Towards Sustainability in the "Flor De Alfalfa" Company - Ayala, Ricardo Ortiz; Pérez, Héctor Fernando Valencia; Hoyo, Marisol Amparo Ríos; Maldonado, Jesús Hurtado (Archives of Business Research, 2023)
In 2015, world leaders adopted a set of global goals to eradicate poverty, protect the planet and ensure prosperity for all as part of a new sustainable development agenda. Each goal has specific targets to be achieved over the next fifteen years. In order to achieve them, the governments, as well as the private sector and civil society, must all do their part. Mexico has taken action toward sustainability and the care of the natural environment, due to the impact of the economic and industrial development. Companies are key to directing the country to an important improvement with regard to sustainability. “Flor de Alfalfa” is a producer of cheese and other dairy products that observes practices aimed at sustainability in its daily activities, which act as the company’s best letter or recommendation, so to speak. In this article, both the company’s sustainability practices their opportunity areas are identified and analyzed. For this, the qualitative methodology and the documentary method were applied, via interviews and observation to analyze the related documents.